Kant’s categorical imperative and republicanism from the perspective of civil society - Caviglia Marconi, Alessandro (2019)
Republicanism has become an important tradition in the debate on political and social philosophy, thanks to the work of Philip Pettit and Rainer Forst. The republican ideology of Immanuel Kant can contribute to enrich the debate on the subject. This paper presents the way in which it is possible to interpret Kant’s categorical imperative so that it allows the conception of republicanism that has its starting point in the civil society. In this sense, the text explores the possibility of a practical and consequentialist interpretation of the categorical imperative, which makes it possible to transmit republicanism from the civil society to the State.